Community structure and total carbon stock analysis of mangrove forests in Abejao and Maliwaliw, Salcedo, Eastern Samar - Canillas, Zynna Mae S.; Malanguis, Jessa May T. (2024)
Mangrove forest is considered one of the most carbon-rich ecosystems in the tropics, and there is growing interest in leveraging them for greenhouse gas emissions mitigation. However, few studies on total carbon stoch (TCS) - accounting aboveground biomass (AGB), belowground biomass (BGB), soil carbon stock - especially in Eastern Visayas, have been conducted to date. Thus, this study aimed to evaluate the community structure and determine the total carbon stock of the two mangrove sites in Abejao and Maliwaliw, Salcedo, Eastern Samar. In each site, four 7m radius circular plots were established at different distances perpendicular to the shoreline: 20 m, 75 m, 185 m, and 250 m. All mature trees were identified, measured, and recorded to evaluate the forest community structure. For soil carbon stock, a 1 m depth soil sample was collected using a German corer. Data analytics and the Loss-on-ignition method was used to quantify the total carbon stock of the mangrove forests. Results show that species diversity in Abejao and Maliwaliw exhibited 'very low' diversity, with H' = 1.29 and H' = 1.022, respectively. Moreover, Abejao and Maliwaliw stored substantial TCS, with sediment carbon stock identified as the largest contributor, comprising 69.09% and 92.43% of the TCS, respectively. Pearson correlation indicated strong positive correlations between the importance value index (IVI) and both AGB C-stock (Abejao: r= 0.88; Maliwaliw: r=0.97) and BGB C-stock (Abejao: r=0.91; Maliwaliw: r=0.99), implying that as the IVI of a species increases, its AGB and BGB C-stock increases as well. Considering the carbon stock accounted from both sites, the mangrove forests in Abejao and Maliwaliw have the potential to store large amounts of carbon despite the very low diversity. By understanding the community structure and TCS of these ecosystems, policymakers and conservationists can make informed decisions to ensure sustainability of mangrove forests.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.